Parâmetros qualitativos da carne de cordeiros submetidos aos modelos de produção orgânico e convencional - Zeola, Nivea Maria Brancacci Lopes [UNESP]; da Silva Sobrinho, Américo Garcia [UNESP]; Manzi, Milani Gabriela [UNESP] (My University, 2011)
This work aimed to evaluate qualitative parameters of meat, sensorial analysis, ivermecin residue and heavy metals from 48 Ile de France lambs submitted to organic and conventional production models which were slaughtered at 32 kg of body weight. Lamb meat from organic model had larger yellowness w to compawithto conventional mo to 45 minutes after the slaught anbut L * and a* parameters were not affeced;, however, not eady the color of lamb meat 24 hours after the slaugter, not influenced by treatments. There was not effect of treatments in pH and temperatureat 45 minutes and 24 hours after the slaughter, in water holding capacity and in shear force, while the cooking losses were influenced by treatments. In the meat of lambs submitted to organic model, the subjective tenderness and the global acceptance were lower when compared to convencional model. Treatments didn't influence arsenic, cadmium and lead meat tenor. Inexistence of ivermectin was verified in meat from organic and conventional production models.
Qualitative parameters of lamb meat submitted to organic and conventional production models
Keywords: Color; Cooking losses; Heavy metals; Tenderness; Water holding capacity; Ovis aries